2008
DOI: 10.1007/s11357-008-9069-9
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent Wnt gene expression in bone and during the course of osteoblast differentiation

Abstract: Wnt signaling is vital for osteoblast differentiation and recently has been associated with aging. Because impaired osteoblastogenesis is a cellular characteristic of age-induced bone loss, we investigated whether this process is associated with an altered expression of Wnt signaling-related proteins in bone and osteoblasts. Bone marrow cells were isolated from male C57BL/6 mice, aged 6 weeks, 6 months, and 18 months, respectively. Osteogenic differentiation was induced for 3 weeks and assessed using alizarin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 27 publications
2
57
0
Order By: Relevance
“…Osteoblastic expression of Wnt-related proteins is modulated by aging. (34) We observed a positive association between sclerostin levels and age. Other studies report increased sclerostin levels with age.…”
Section: Discussionmentioning
confidence: 49%
“…Osteoblastic expression of Wnt-related proteins is modulated by aging. (34) We observed a positive association between sclerostin levels and age. Other studies report increased sclerostin levels with age.…”
Section: Discussionmentioning
confidence: 49%
“…7). The finding that PTH at low dose is able to modulate specific Wnt signalling effectors in Samp6 mice is particularly important in the context of skeletal senescence because results from current studies indicate that bone ageing is associated with alterations in the local expression of Wnt ligands (Rauner et al 2008) among other mechanisms (Manolagas & Parfitt 2010, Marie 2014. We previously reported that the anti-osteoporotic agent strontium ranelate promotes Wnt signalling in osteoblasts and thereby increases bone formation and bone mass in senescent osteopenic Samp6 mice (Saidak et al 2012).…”
Section: Wisp1 Mef2cmentioning
confidence: 99%
“…Although in situ hybridisation studies have not detected Wnt1 expression during in utero mouse limb development,20 Wnt1 expression can be detected by real-time PCR in postnatal mouse long bones, including osteoblasts 21. Given the predominance of the brain phenotype in the global Wnt1 knockout mouse, this mouse model may not be ideal for elucidating the function of Wnt1 in bone cells.…”
mentioning
confidence: 96%